Molecular detection of uncultured cyanobacteria and aminotransferase domains for cyanotoxin production in sediments of different Kenyan lakes - Dadheech, Pawan K.; Krienitz, L.; Kotut, Kiplagat; Ballot, A.; Casper, P. (Blackwell Publishing Ltd, 2009)
PCR-based denaturing gradient gel electrophoresis (DGGE) analysis of 16S rRNA gene fragments was used to identify the cyanobacterial phylotypes in sediments and plankton of saline–alkaline and freshwater lakes of Kenya. The detection of the aminotransferase domain located on modules mcyE and ndaF using specific molecular markers confirmed the presence of potential toxin-producing cyanobacteria. The eight nucleotide sequences obtained from DGGE bands were placed in three divergent cyanobacterial clusters. Five nucleotide sequences were close to members of the genera Anabaenopsis and Umezakia (Nostocales), two sequences fell in the cluster with Arthrospira sp. (Oscillatoriales) and one sequence was related to Chroococcidiopsis sp. (Pleurocapsales). The presence of the latter taxon was demonstrated de novo in the investigated lakes. All nine attained nucleotide sequences of the aminotransferase region belonged to the mcyE module. Five sequences of the aminotransferase domain were included in the cluster having the nucleotide sequence of Anabaena sp. but showed a separate lineage. Other four aminotransferases were placed in the cluster represented by nucleotide sequence of Microcystis aeruginosa. To our knowledge, this is the first report on molecular detection of cyanobacterial phylotypes in sediments of African lakes and aminotransferase domains for cyanotoxin production from sediment samples in general.
DOI:10.1111/j.1574-6941.2009.00678.x
Keywords: Cyanobacteria; sediment; aminotransferase; Cyanotoxins; lake; Kenya